Development of a Drug and Health Consumer Protection Competency Assessment Tool for Pharmacists - Chuethammachan, Wanna (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
The purposes of this research were to develop a drug and health consumer protection performance assessment tool and examine the health consumer protection performance assessment of pharmacists under the Nonthaburi Provincial Public Health Office. The sample was 67 pharmacists under the Nonthaburi Provincial Public Health Office. The research tool was developing by Delphi technique, with 5 expert pharmacists to give multiple rounds of opinions, each of which used the comments to calculate the frequency of each question and summarize the answers to the next round as information for the next round of comments. If in any round the frequency of 80 percent or more agrees on all of them, then in that round there was a consistent opinion and the process was terminated. The conclusions showed that the criteria for evaluating drug and health consumer protection competencies consisted of four competencies: legal and law enforcement, consisting of 12 questions, risk management system, epidemiology and drug safety, consisting of 25 questions, policy and drug management consisted of 10 questions and the health products and healthcare system consisted of 9 questions. The quality of assessment tool found that the consistency between each question and the objective congruence (IOC) was greater than 0.5 for every question and the reliability check was obtained by Cronbach's alpha coefficient. The value was equal to 0.990. Then evaluated the competency of pharmacists under Nonthaburi province by sending a questionnaire by postal mail. There were 57 responses, equivalent to 85.07 percent. The results showed that the average competency of pharmacists performing consumer protection tasks had a higher level of competency than pharmacists who did not perform consumer protection work. And the average competency of pharmacists performing consumer protection tasks was statistically significantly different from pharmacists who do not perform consumer protection work. (p < 0.05)